Mortality trends from suicide by state and socioeconomic region. Mexico, 2000-2016 - Sánchez-Barriga, Juan Jesús (Papeles de Población, 2023)
Objective. To determine mortality trends from suicide at the national level, by state and socioeconomic region, as well as determine the risk of suicide, according to the level of schooling and socioeconomic region in the period from 2000 to 2016. Methods . Mortality records for intentionally self-inflicted injuries were obtained for the period 2000-2016. The strength of association (obtained by Poisson regression) of socioeconomic regions and level of education with suicide was determined. Results Age-adjusted suicide rates per 100,000 inhabitants increased from 3.7 to 5.1. Individuals without schooling or incomplete elementary school had a higher risk of suicide (RR 4.603, CI95% 4.601-4.604). Socioeconomic region 5 had the highest mortality and relative risk of suicides. Conclusions . Age-adjusted suicide rates per 100,000 inhabitants increased from 3.7 to 5.1 between 2000 and 2016. Individuals without schooling or incomplete elementary school had an increased risk of suicide.